The Psychological Health Status of Healthcare Workers During the COVID-19 Outbreak: A Cross-Sectional Survey Study in Guangdong, China - Li, Qing; Chen, Jinglong; Xu, Gang; Zhao, Jun; Yu, Xiaoqi; Wang, Shuangyan; Liu, Lei; Liu, Feng (Frontiers in Public Health, 2020)
Background: The sudden outbreak of COVID-19 has caused mental stress on healthcare workers (HCW). This study aimed to assess their psychological health status at the peak of COVID-19 and to identify some coping strategies. Methods: A cross-sectional survey study was conducted during the outbreak of COVID-19. The survey was completed by 908/924 HCW (response rate 98.27%) in government-designated hospitals in Guangdong, China. A quality of life (QoL) scale, the Zung Self-Rating Anxiety Scale (SAS), and the Zung Self-Rating Depression Scale (SDS) were used to evaluate their psychological status. Logistic regression models were used to identify the occupational factors related to anxiety or depression. Results: A total of 221 (24.34%) respondents had varying levels of anxiety, and 299 (32.93%) of them had depression. The mean SAS (42.9) and SDS (47.8) scores of HCW indicated that they were in the normal range for both anxiety and depression. Contact with COVID-19 cases or suspected cases, worry about suffering from COVID-19, worry about their family, and dismission during the COVID-19 period were significant work-related contributing factors to the psychological health problems of HCW (all p<0.01). Conclusions: The overall psychological health status of HCW in Guangdong, China, during the outbreak of COVID-19 was not overly poor. Updating and strengthening training in disease information, the provision of adequate medical supplies, and care about the life and health of medical staff and their family members may reduce their mental stress.